2019
DOI: 10.1103/physrevb.100.165304
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and hyperbolic dielectric properties of ZrS2/HfS2 heterostructures

Abstract: In this paper we investigate the electronic and optical dielectric properties of lateral and vertical heterostructures composed of two-dimensional (2D) ZrS2 and HfS2 monolayers based on density functional theory. First, we show that the bulk and monolayer ZrS2 and HfS2 as well as the vertical (ZrS2)m/(HfS2)n heteroestructures are indirect band gap semiconductors, while the lateral heterostructures exhibit an indirect to direct bandgap transition. Then we demonstrate that the optical properties of the bulk and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…65 Recently, it has been found that some 2D materials, such as Bi 2 Te 3 , phosphorene and ZrS 2 /HfS 2 VDWHs, also exhibit hyperbolic properties. 66,67 Compared with traditional metamaterials, these natural hyperbolic materials with thicknesses of atomic scale can not only cut back the limitations of the finite size of the unit cell in artificial hyperbolic structures, but also have no internal interface to scatter electrons. However, to the best of our knowledge, there is no research on the hyperbolic properties of selenene or Se-based materials.…”
Section: Optical Properties Of the A-se-based Vdwhsmentioning
confidence: 99%
“…65 Recently, it has been found that some 2D materials, such as Bi 2 Te 3 , phosphorene and ZrS 2 /HfS 2 VDWHs, also exhibit hyperbolic properties. 66,67 Compared with traditional metamaterials, these natural hyperbolic materials with thicknesses of atomic scale can not only cut back the limitations of the finite size of the unit cell in artificial hyperbolic structures, but also have no internal interface to scatter electrons. However, to the best of our knowledge, there is no research on the hyperbolic properties of selenene or Se-based materials.…”
Section: Optical Properties Of the A-se-based Vdwhsmentioning
confidence: 99%
“…The dispersion relation represents the allowed propagation directions and their corresponding wavelengths. Moreover, the photonic density of states (PDOS) increases because the unique hyperbolic unlimited wave vectors (i.e., high- k modes) of the iso-frequency contour in the momentum space. Once the metal and the dielectric interface is thin and flat, a collective oscillation of electrons called surface plasmon polaritons (SPPs) is confined to the interface. In addition, the high- k modes that emerge from the intercoupling effect of SPPs are realized as the volume plasmon polaritons, resulting in an enhancement of charge-transfer dynamics, an improvement in fluorescence emission, incremented transition rates of optical gain media, and a higher possibility of achieving laser action. , …”
Section: Introductionmentioning
confidence: 99%
“…HfS 2 , as a member of the transition metal dichalcogenides, has recently emerged as a promising material for electronics and energy conversion applications in the semiconductor community due to its sizeable bandgap and other favorable physical properties. [1][2][3][4][5][6][7][8][9] In comparison to its bulk counterpart, thin film HfS 2 has shown further intriguing properties. 1,10 The methods reported so far for the synthesis of thin film HfS 2 have been mechanical exfoliation and chemical vapor deposition.…”
Section: Introductionmentioning
confidence: 99%